Combining experts’ knowledge and meta-analysis in prioritizing and packaging Climate Smart Agricultural (CSA) practices in Ethiopia - Adimassu, Zenebe; Tibebe, Degefie; Abera, Wuletawu; Tamene, Lulseged D. (2023)
It is widely acknowledged that climate smart agricultural (CSA) practices prioritization is influenced by subjectivity and relies heavily on the expertise and exposure of the experts. The objective of this paper is to enhance the precision and objectivity of prioritizing CSA practices by leveraging a combination of research findings and expert knowledge. This is the first attempt to integrate experts’ knowledge and meta-analysis in the prioritization of CSA practices. Before integrating the two ranks, separate approaches were used to prioritize and rank CSA practices. The steps taken include: i) CSA prioritization assessment framework was used to identify and prioritize CSA practices across various agro-ecologies based on the CSA pillars (productivity, adaptation and mitigation), ii), meta-analysis approach was employed to determine the effect size of various CSA practices on the three pillars of CSA practices, iii), the effect size values were rescaled and ranked based on effect size categories, and iv), correlation was performed to assess the relationship between the two approaches, and finally, average values were taken to integrate and determine the final rank of CSA practices. Generally, the study showed that there is a mismatch between the ranks of CSA practices by experts and meta-analysis results. This is explained by lack of correlation between the ranks of the two approaches. The result showed that only 35% of the CSA practices got equal rank by both approaches, 40% of the CSA practices got higher rank by experts while 25% of the CSA practices got higher rank using meta-analysis approach. This implies that experts over-estimated the effect of various CSA practices on various indicators of productivity, soil loss, and run-off and soil organic matter. Integrating the ranks of the two approaches helped to target CSA practices across various agro-ecological zones. According to the combined ranks, several CSA practices were targeted to six major agro-ecological zones of the country. These CSA practices are combinations of physical, biological, agronomic increased productivity, reduced soil loss and run-off (adaptation) and enhance soil organic matter (sequestration). Base on the availability of these CSA practices, it is possible to package various combinations of these practices presented in Table 7. Since meta-analysis was based on the experimental data and was not exhaustive, it was difficult to provide CSA practices for across all indicators. Hence, it is important to update the meta-analysis study in the coming years.